Construção de vetores de expressão para Escherichia coli baseados em promotores ativos na fase estacionária de crescimento - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
Plasmids are extrachromosomal genetic elements that generally are not essential for survival of the bacteria , however , provide unique advantages ( as resistance to antibiotics) for the organism. For genetic engineering, naturally occurring plasmids have been modified extensively for the production of vectors with the desired characteristics. Promoters are elements of a vector which may have a profound effect on the strength and duration of transcription and, consequently, the protein yield . The mRNA synthesis starts when RNA polymerase binds the promoter sequence adjacent to the target gene. Sigma factors are proteins that regulate transcription in bacteria , and they can be activated in different environmental conditions . The sigma factor ( S ) is seen as a master regulator of the general stress response , encoded from the gene RpoS in late stationary phase . This factor is the primary regulator of the genes stationary phase . Prosecutors based metabolic regulators of stationary phase represent a class of promoters metabolically controlled and can be exploited for the design of expression vectors . This project were developed three expression cassettes for construction of expression vectors , which have promoters with affinity for sigma factor S , in order to evaluate the expression profile of recombinant proteins in Escherichia coli . To evaluate the strength of promoters and expression profiling , we used the green fluorescent protein ( GFP ) as a reporter gene . The three vectors constructed, which were named p26 , p53 and PFS expressed GFP in the correct formation of the fluorophore , and the vector p26 and p53 showed overexpression of the recombinant protein when compared to the vector pGS21a . Furthermore , it was observed that the vectors constructed here are contributing to the reduction in the rate of growth and filamentation of E. coli. This gives the morphological plasticity bacterium higher storage capacity of the recombinant protein expressed .
Keywords: Vetores de expressão; Escherichia coli; Promotores; Fase estacionária; GFP; Expression vectors; Escherichia coli; Promoters; Stationary phase, GFP; CIÊNCIAS BIOLÓGICAS